Pendampingan Pengelolaan Keuangan untuk Mendorong Peningkatan Pendapatan Pengelola Objek Wisata Tampang Allo - Westerini Lusdani; Yohanis Lotong Ta’dung; Chrismesi Pagiu; Rati Pundissing (Institut Nalanda, 2026)
Tampang Allo Tourism Object is one of the local tourism potentials that can be developed as a source of community income. However, financial management that has not been planned and structured properly remains one of the main obstacles in optimizing tourism revenue. This community service activity aims to improve the understanding and skills of tourism managers in recording financial transactions, preparing simple financial reports, classifying sources of income and expenses, and planning the use of funds more effectively. The activity was implemented using a participatory approach through initial observation, interviews, problem identification, financial management training, practical mentoring, monitoring, and evaluation. The results show that the managers began to understand the importance of recording income and expenses regularly, separating operational funds, and using financial reports as a basis for determining tourism development priorities. This mentoring activity also encouraged the involvement of managers and the local community in managing tourism revenue more transparently and responsibly. The implication of this activity is the improvement of managers’ capacity in organizing tourism financial management, which can support decision-making, cost control, facility maintenance, promotion, and sustainable income growth.